Adult education and social inclusion in Chile - Oscar Espinoza Díaz; Programa Interdisciplinario de Investigaciones en Educación (PIIE), Centro de Políticas Comparadas en Educación, U. Diego Portales y Centro de Investigación en Educación, Universidad UCINF; Dante Castillo; Programa Interdisciplinario de Investigaciones en Educación (PIIE) y Centro de Investigación en Educación, Universidad UCINF; Luis Gonzalez Fiegehen; Programa Interdisciplinario de Investigaciones en Educación (PIIE) y Centro de Investigación en Educación, Universidad UCINF.; Juan Carlos Santa Cruz; Centro de Investigación en Educación, Universidad UCINF (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2014)
Despite the large number of people with incomplete schooling currently observed in Chile, back-to-school programs have not been a government priority. This article analyzes the profiles of students that use this type of programs, and the degree to which this leads to social inclusion and dynamics. In order to characterize them, we used a survey filled out by beneficiaries of back-to-school programs and a social inclusion index. The analysis of these programs reveals a complex reality, with large differences, both across the various types of programs and inside them. Some people do integrate into the system. They have a steady job and up bring their families, while some others are more vulnerable and at social risk. These situations map into a wide spectrum of social problems, different levels of societal and job insertion, and unequal future expectations.  These differences reveal different degrees of inclusion or exclusion at the system level, which in turn compel the Administration to deal with adult education, facing that there is a diversity of realities, regardless of the level of vulnerability of this population.